Ecomuseum, community museology, local distinctiveness, Hüsamettindere village, Bogatepe village, Turkey. Issue 1 (18th May 2015) - Dogan, Mustafa
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The concept of sustainable development is now widely accepted as a means of protecting natural resources and cultural heritage. One approach to ensuring sustainability, especially in relation to cultural tourism, is the ecomuseum. Turkey has considerable potential to develop ecomuseological models to encourage local sustainable development. The purpose of this paper is to explore the development of ecomuseums in Turkey by analysing the recent implementation of the concept in Hüsamettindere and Bogatepe villages. Current practices at these two sites are evaluated in comparison with the basic principles of ecomuseum theory. Design/methodology/approach – This paper explores local community involvement in two emerging ecomuseums in Turkey based on several years of participant action research by the author; it describes the nature of the two ecomuseums based on that experience. In addition an in-depth survey was carried out between February and April 2013 by Canakkale Onsekiz Mart University when 45 local participants were interviewed for their views on the ecomuseum developments, using the MACDAB method (Borrelli et al., 2008) as a guide. Findings – Even though the two implementations in Turkey have different features deriving from their local dynamics, they have had a similar experience in terms of the development process. Both began with a volunteer movement, the organisation of the local community, the formation of civil initiatives, a joint decision-making processes and the existence of participation and consensus. This process conforms to the basic principles of ecomuseology. The ecomuseums have also raised concerns about the loss of rural heritage and the mechanisms for conserving it within the model of the "living" ecomuseum. The most significant fact to emerge from this initial review of the two ecomuseums is that it is not necessarily their ability to conserve fragments of tangible and intangible heritage that is paramount in Turkey, but their importance in providing employment opportunities in rural areas. Originality/value – Ecomuseum movement is a very important and practical model for sustainable development and tourism. Ecomuseums can also be functional tools for protecting of cultural heritage and developing of local areas. Even though Turkey has got many cultural heritage sources, they are not used productively for local sustainable development. The two implementations will be sample to all natural and cultural heritage areas of Turkey for sustainable development.